Using three AOSE toolkits to develop a sample design. (20th May 2009) - DeLoach, Scott A.; Padgham, Lin; Perini, Anna; Susi, Angelo; , John Thangarajah
At the 8th Agent-Oriented Software Engineering Workshop, the developers of tools supporting three popular agent-oriented methodologies (Tropos, Prometheus and Organization-based Multiagent Systems Engineering (O-MaSE)) demonstrated their tools using a common multi-agent system design case study: the Conference Management System. The methodologies are representative of the state-of-the-art in agent-oriented software methodologies, as they are some of the earliest and most mature agent-oriented methodologies currently available. The paper briefly summarises the three methodologies and their associated tools and then works through the analysis, architectural design and detailed design phases of the Conference Management system case study using each methodology and tool. The paper compares the models and concepts used during each phase and provides a discussion on the similarities and differences between them.